Implementasi Pembelajaran Aktif untuk Meningkatkan Keterlibatan Siswa di Sekolah Dasar (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Active learning is an instructional approach that positions students as central participants in the learning process through interactive, collaborative, and reflective activities. This study aims to examine the implementation of active learning strategies in enhancing student engagement at the elementary school level. A literature review method was employed, analyzing 20 national and international scholarly articles published between 2019 and 2024. The findings indicate that strategies such as Problem-Based Learning, cooperative learning, and experiential learning effectively increase students' participation, motivation, and academic achievement. The integration of digital media and educational games also contributes positively to students’ focus and emotional engagement during lessons. However, several implementation challenges were identified, including limited teacher competence, insufficient learning facilities, and time constraints within the curriculum. These findings highlight the importance of policy support, continuous teacher training, and the provision of adequate learning resources to ensure the optimal application of active learning in elementary classrooms. Therefore, active learning emerges as a strategic solution to improve the quality of primary education by fostering student-centered and engaging learning experiences.